European administrative networks, private networks and agencies: coexisting, cooperating or competing? - Eckert, Sandra (Journal of European public policy, 2022)
Little attention has been paid to the relations between European agencies and regulatory networks in existing research, and the role of private networks has not been considered. This article fills this research gap and examines when sectoral bodies coexist, cooperate or compete. It develops a conceptual framework to map the diversity of sectoral bodies, and identifies mission- and resource-related explanatory factors for types of interaction. The qualitative comparison analyses a case with multiple public bodies (banking), as opposed to a case with agency and network structures as well as public and private bodies (electricity). The findings support arguments in existing research, namely that cooperation is driven by resource complementarity and mission overlap. Further, they point to the relevance of mission and resource rivalries as explanations for conflictual relations, and show that resource- and mission-related factors materialise very differently across distinct institutional settings. The conceptual framework paves the way for further cross-sectoral analysis of inter-organisational relations in the European administrative space.
CRIS-Team WoS Importer:2022-09-09